Um estudo sobre o perfil de estudantes de ensino médio nos documentos oficiais e em escolas estaduais de Goiania - GO - Silva, Érivan Cristina (2016)
The current study aimed to describe the profile of high school students from state schools in Goiânia. In order to achieve the results, a qualitative approach was employed, so that the research elements could be understood in their complexity. This study was developed in four steps: analysis of legal guiding education documents in Brazil and in Goiás; submission of questionnaires to 348 high school students (3rd grade) from 12 state schools in Goiânia; semi-structured interviews with 12 school teachers, in which questionnaires were applied and analysis and discussion of the results obtained in these documents, questionnaires and interviews. Collected data were examined by documentary analysis and through content and descriptive statistical analysis, which led to the following categories of analysis: 1) citizenship, from which emerged the subcategories: a) gender/ethnicity and b) access to cultural assets; and 2) training for work and further studies. Analyzing the given categories showed that describing the students profile in Goiânia made us realize that it is not enough to guarantee the access to school. Students believe that they can improve their lives through access to the literate world, and that, by accessing formal studies, they may be able to achieve better professional opportunities, which will lead them to a better socioeconomic situation than the one they currently belong. Students also believe that, in addition to learning, they can interact with teachers and colleagues. Young high school students’ profile in Goiânia indicates that, in order to face the challenges of education in general, and the teaching of sciences in particular, the previous existence of each one must be considered, that is, the history of every student. Those who collaborated with this work reported a low level of access to the cultural assets available in Goiânia, which does not mean that they do not own cultural assets.